Employee Problems and Their Consequences in the Technology Industry: Evidence from Surveys and Counseling Records. Issue 3 (June 2014) - Wang, Ching-Wen; Lin, Po-Chang; Sha, Chyuan
To support employees' work and health, organizations should help employees cope with common problems. Previous studies have focused primarily on work-related problems across multiple industries rather than on evaluating industry-specific issues. Here, two approaches identified common work and nonwork employee problems in the technology industry with the strongest correlations with psychosomatic health and life satisfaction. Study 1 used questionnaires to identify the problems that were perceived as the most frequent by lower-level employees ( N =355) working in the technology industry. Study 2 evaluated employees' coping behaviors by analyzing (with permission) counseling records collected from an employee assistance service company ( N =276). Employees reported a variety of problems; work problems were the only problems (of the top 5 problems) reported in both studies. Several problems emerged in the counseling records (e.g., legal issues, career development, family and marriage problems, and emotional problems) but not in the surveys. Future research should apply these observations to develop scales for measuring employee stressors.